Wintering snow buntings elevate cold hardiness to extreme levels but show no changes in maintenance costs - Le Pogam, Audrey; Love, Oliver P.; Régimbald, Lyette; Dubois, Karine; Hallot, Fanny; Milbergue, Myriam; Petit, Magali; S. O’Connor, Ryan; Vézina, François (Physiological and Biochemical Zoology, 2020)
Resident temperate passerines adjust their phenotypes to cope with winter constraints, with peak performance in metabolic traits typically occurring during the coldest months. However, it is sparsely known whether cold-adapted northern species make similar adjustments when faced with variable seasonal environments. Life in near-constant cold could be associated with limited flexibility in traits underlying cold endurance. We investigated this by tracking individual physiological changes over five consecutive winters in snow buntings (Plectrophenax nivalis), an Arctic-breeding migratory passerine typically confronted with nearly constant cold. Buntings were held in an outdoor aviary and exposed to seasonal temperature variation typical of temperate zone climates. We measured phenotypic changes in body composition (body, fat, and lean mass, pectoralis muscle thickness), oxygen transport capacity (hematocrit), metabolic performance (basal metabolic rate [BMR] and summit metabolic rate [Msum]), thermogenic endurance (time to reach Msum), and cold tolerance (temperature at Msum). Snow buntings showed flexibility in functions underlying thermogenic capacity and cold endurance comparable to that observed in temperate resident passerines wintering at similar latitudes. Specifically, they increased body mass (13%), fat mass (246%), hematocrit (23%), pectoralis muscle thickness (8%), and Msum (27%). We also found remarkable cold tolerance in these birds, with individuals reaching Msum in helox at temperatures equivalent to less than 2907C in air. However, in contrast with resident temperate passerines, lean mass decreased by 12%, and there was no clear increase in maintenance costs (BMR). Our results show that the flexibility of traits underlying thermal acclimatization in a cold-adapted northern species is comparable to that of temperate resident species living at lower latitudes and is therefore not limited by life in near-constant cold.